2020
DOI: 10.1002/gps.5261
|View full text |Cite
|
Sign up to set email alerts
|

Neuroticism predicts fear of falling after hip fracture

Abstract: Objectives Fear of falling (FoF) is common and associated with poorer functional outcomes after hip fracture. We sought to differentiate patterns of FoF at 4 and 12 weeks after surgical repair for hip fracture and examine predictors of FoF. Methods/design Secondary analysis of existing data from a 52‐week prospective study examining recovery after hip fracture. Participants (N = 263) were aged 60 and older with recent hip fracture recruited from eight hospitals. FoF was measured 4 and 12 weeks postfracture wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 59 publications
1
19
1
Order By: Relevance
“…In men, poor physical fitness and lower limb relative appendicular lean mass accelerate cortical bone loss and increase the risk of falls, leading to hip fracture ( 75 ). In addition, recent research suggests that people with a fall phobia are more likely to fall in the first 12 weeks after a hip fracture because of their high degree of neuroticism ( 76 ). A cross-sectional study reported that the combination of sarcopenia and osteoporosis potentially increases the risk of hip fracture ( 77 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In men, poor physical fitness and lower limb relative appendicular lean mass accelerate cortical bone loss and increase the risk of falls, leading to hip fracture ( 75 ). In addition, recent research suggests that people with a fall phobia are more likely to fall in the first 12 weeks after a hip fracture because of their high degree of neuroticism ( 76 ). A cross-sectional study reported that the combination of sarcopenia and osteoporosis potentially increases the risk of hip fracture ( 77 ).…”
Section: Resultsmentioning
confidence: 99%
“…Internal mental health is also an issue that requires attention. Patients with a fall phobia are more likely to fall in the first 12 weeks after hip fracture because of their neuroticism ( 76 ). Therefore, it is essential to provide all-round psychological counseling to people who have fallen.…”
Section: Resultsmentioning
confidence: 99%
“…For clinical practice it seems relevant to monitor the course of FoF. Findings from a cohort study of hip fracture patients show three distinct patterns of FoF evolving from 4 to 12 weeks after fracture; i] patients with consistently low levels of FoF; ii] patients with high levels of FoF at 4 weeks that continue to increase; iii] patients with high levels of FoF at 4 weeks which decrease at 12 weeks post-fracture [38]. It is currently unknown how these distinct trajectories relate to avoidance behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor to consider when screening for FoF, is the (mediating) role of anxiety (traits) in the development of maladaptive or dysfunctional fear of falling [18,39,40]. Findings from Bower et al show that patients with higher scores for neuroticism were more likely to have high levels of FoF [38]. Also, the previously mentioned in-home cognitive behavioral program for FoF that was conducted by physiotherapists and showed positive effects on reducing FoF and activity restriction, was aimed at patients with disproportionate FoF; as defined as high fear and low to moderate objective fall risk and functional impairment because of FoF [29].…”
Section: Discussionmentioning
confidence: 99%
“…Fear of falling, along with impairment of balance and walking abilities are further factors. Fear of falling is reported by more than half of individuals with previous HF, and can influence functional abilities [256], physical recovery [257,258], and emotional stability [257]. Balance impairment can significantly reduce mobility, also increasing the risk of falls.…”
Section: Risk Of Fall Evaluation and Managementmentioning
confidence: 99%